Wpływ wieku, menopauzy, ćwiczeń mięśni miednicy, zwiększonej ruchomości cewki moczowej, zabiegów chirurgicznych na wyniki operacji z zastosowaniem taśmy przeprowadzonej przez otwory zasłonowe (czynniki wpływające na wyniki operacji z zastosowaniem metody TOT) - Yavuzcan, Ali; Yıldız, Gazi; Üstün, Yusuf; Altıntaş, Raşit; Çağlar, Mete; Yıldız, Pınar; Sert, Hüseyin; Dilbaz, Serdar; Kumru, Selahattin (Menopause Review/Przegląd Menopauzalny, 2013)
Objectives: We evaluated age, menopause, Q-tip and urinary stress tests performed on an outpatient basis before the transobturator tape (TOT) procedure, preoperative Kegel exercises, and vaginal surgeries performed concomitantly with the TOT procedure for their impact on symptomatic relief and complications in patients undergoing the TOT procedure. Aim of the study: Data including age, parity, menopausal status, concomitant vaginal surgery, complications, whether or not preoperative Kegel exercises were administered and urinary (cough) stress test and Q-tip test were performed, were retrieved from the patient charts and hospital records. Material and methods: The medical records of women, who underwent the TOT procedure for SUI in the Department of Obstetrics and Gynecology in Bucak State Hospital between January 2009 and November 2012 were reviewed. Results: No significant difference was observed between patients below and at or above 50 years of age in terms of success rate and complication rate (p = 1.00 and p = 0.351, respectively). There was a tendency for menopausal women to have a higher success rate (93.3% vs. 75%), this did not reach a statistical significance (p = 0.09). Urethral hypermobility did not significantly influence the success rate and complication rate (p = 0.694). Kegel exercises did not significantly influence the success rate and complication rate (p = 0.694). Vaginal surgeries performed concomitantly with the TOT procedure did not significantly influence complication rate (p = 0.454). Conclusions : The TOT procedure brings about the high success and low complication rates. Prospective, randomized, controlled studies on a larger number of patients are needed to clearly identify factors that would raise the success rate and reduce the complication rate.